Left-Shifted Nav Channels in Injured Bilayer: Primary Targets for Neuroprotective Nav Antagonists? - Morris, Catherine E.; Boucher, Pierre A.; Joos, Bela (Frontiers in Pharmacology, 2012)
In sodium channel (Nav)-rich axon initial segments and nodes of Ranvier, mechanical, ischemic and inflammatory injuries render these voltage-gated channels dangerously leaky. Extrapolating from recombinant Nav1.6 behavior (Wang et al 2009 Am J Physiol 297:C823), we postulate that the structural degradation of axolemmal bilayer, a common feature of neuoropathologic conditions, fosters ENa dissipation by favoring left-shifted Nav channel operation. This “sick excitable cell Nav-leak” would encompass left-shifted Itransient and Ipersistent components (fast-mode Iwindow, slow-mode Ipersistent). Ideally, bilayer damage-induced malfunction of Nav channels could be studied in Nav-rich myelinated axon nodes, exploiting the INa(v,t) hysteresis of sawtooth ramp voltage clamp. We hypothesize that protective lipophilic Nav antagonists (e.g., ranolazine, riluzole) partition more avidly into disorderly bilayers of traumatically (ischemically, etc) damaged axons than into well-packed undamaged bilayers. Whereas inhibitors using aqueous routes would access all Navs equally, differential partitioning into “sick bilayer” would co-localize lipophilic antagonists with “sick Nav channels”, allowing for more specific targeting of impaired cells. Molecular fine-tuning effective antagonists for maximal partitioning into damaged-membrane milieus (thereby avoiding healthy cells) could help reduce Nav antagonist side-effects. In potentially salvageable neurons of traumatic and/or ischemic penumbra, in inflammatory neuropathies, in muscular dystrophy, in myocytes of cardiac infarct borders, Nav-leak driven excitotoxicity too easily overwhelms cellular repair mechanisms. Precision-tuned Nav antagonist variants that preferred mildly, as opposed to severely, damaged Nav-rich axolemma or sarcolemma might be suitable for the prolonged continuous administration needed to allow for excitable cell remodeling and hence for improved functional recovery.